2019
DOI: 10.1002/rcm.8476
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative reconstruction of salinity history by otolith oxygen stable isotopes: An example of a euryhaline fish Lateolabrax japonicus

Abstract: Rationale:Otolith strontium:calcium (Sr:Ca) ratios have been extensively used to study fish migration across a river, estuary and ocean at each life stage. However, otolith Sr:Ca ratios only explain partial variations in salinity and quantitative reconstruction of salinity history of fishes remains a challenge. Using a euryhaline fish Lateolabrax japonicus as an example, this study demonstrated an isotopic method of quantitatively reconstructing the salinity histories and habitat uses of the fish. Methods:Otol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Some fish (Pk2, Pk4, Pk6, Pk7) showed very low otolith δ 18 O values of −4‰ to −5.2‰ in the translucent zones of the otoliths. These lower isotopic values suggested the residency of the fish in the brackish waters of coastal areas or the estuaries in the warm seasons of the year as was found in other teleostean fish 23,24 . Rivers in Taiwan are characterized by radical change in seasonal flow as the major water source is the rain brought by typhoons and monsoons from May to October.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Some fish (Pk2, Pk4, Pk6, Pk7) showed very low otolith δ 18 O values of −4‰ to −5.2‰ in the translucent zones of the otoliths. These lower isotopic values suggested the residency of the fish in the brackish waters of coastal areas or the estuaries in the warm seasons of the year as was found in other teleostean fish 23,24 . Rivers in Taiwan are characterized by radical change in seasonal flow as the major water source is the rain brought by typhoons and monsoons from May to October.…”
Section: Discussionmentioning
confidence: 76%
“…These lower isotopic values suggested the residency of the fish in the brackish waters of coastal areas or the estuaries in the warm seasons of the year as was found in other teleostean fish. 23,24 Rivers in Taiwan are characterized by radical change in seasonal flow as the major water source is the Therefore, the otoliths found in archeological sites or sediments can be used to reconstruct the ancient environments experienced by the fish. Besides, we also found that the δ 18 O value between the check rings could sometimes drop to À4‰ to À5‰, and it may well be the result of the affluent freshwater flow to the coast during the summer periods or the fish migration to the estuaries.…”
Section: Discussionmentioning
confidence: 99%
“…Other than seawater temperature, seasonal fluctuations in primary productivity and food supply may also affect the deposition of translucent and opaque zones in the otoliths of S. commerson [24]. This phenomenon is observed in numerous subtropical and tropical species, in which opaque zones develop in otoliths during the cold season when fish metabolism is lower, and translucent zones develop during periods of accelerated growth (e.g., [39,40]).…”
Section: Age Validationmentioning
confidence: 99%
“…In the case of marine fish, the 18 O: 16 O ratio (d 18 O) in otoliths is the most frequently used isotope ratio for iso-logging (e.g. Trueman et al, 2012;Hsieh et al, 2019;Sakamoto et al, 2019). d 18 O can be retrospectively measured from otoliths and reflects the ambient temperature experienced by the fish.…”
Section: Introductionmentioning
confidence: 99%